Changes in cardiovascular risk factors in patients undergoing first time coronary revascularization from 2003–2020, A nationwide population study. (3rd October 2022) - Pham, M; Christensen, D M; Kristensen, A T; Clausen, C S; Gislason, G H; Olsen, N T
Abstract: Introduction: Current knowledge of cardiovascular risk factors is primarily based on older studies that may not reflect current populations. Monitoring risk factors may influence decisions about prevention and treatment of ischemic heart disease. We hypothesize that the prevalence of traditional risk factors in patients undergoing first-time coronary revascularization has changed over time. Purpose: We examined the proportion of patients with traditional cardiovascular risk factors from year 2003–2020 in patients undergoing first-time coronary revascularization. Methods: We identified all adults undergoing first-time coronary revascularization (percutaneous intervention and bypass grafting) from 2003–2020 using Danish nationwide registries. Risk factors were defined as either medical prescriptions or diagnosis prior to first-time revascularization. We calculated the proportion of individual risk factors per year with associated 95% CI, and calculated the trend using chi-squared test for trend in proportion. Results: We identified 152, 692 patients who underwent first-time coronary revascularization. 78.5% of the patients underwent percutaneous coronary intervention and 21.5% underwent coronary artery bypass grafting, 73.8% were male, mean age 65 (SD 11.5), and 67.9% had at least 1 risk factor at first-time revascularization. Figure 1 shows the trends in risk factors from 2003 to 2020. From 2003–2005 to 2018–2020, the proportion of patients with at least 1 risk factors changed from 70.9 to 64.0%, hypertension changed from 41.4 to 36.0%, hypercholesterolemia decreased from 47.6 to 43.6%, aspirin use decreased from 52.4 to 32.06%, diabetes increased from 11.7 to 15.8%, chronic kidney disease increased from 2.4 to 4.4%, and chronic obstructive pulmonary disease increased from 4.95 to 4.96% (p-value for trend <0.001 for all risk factors, except chronic obstructive pulmonary disease (p-value 0.96)). Conclusion: We assessed the temporal trends in coronary risk factors over a 17-year period in patients undergoing first-time coronary revascularization. We found a large decrease in the proportion of patients with any risk factor, hypertension, hypercholesterolemia, and aspirin use, and an increase in diabetes and chronic kidney disease. The proportion of patients with chronic obstructive pulmonary disease was unchanged. Funding Acknowledgement: Type of funding sources: None.